Moderating role of management support in the relationship between human resource practices and employee performance: A study of academics in Nigerian Polytechnics - Bida, Mohammed Jibrin (2018)
Organisation performance centres on human resource because it has the skills, knowledge and competencies required for the execution of organisational strategy and planning. Considerable numbers of HRM research have indicated positive effects of HR practices on employee performance. Nevertheless, some other studies indicate otherwise, which suggests that findings of the extant research are seemingly inconclusive. Thus, this study investigated the effect of HR practices involving recruitment and selection, training and development, compensation, performance appraisal, and succession planning on employee performance with management support as a moderator. A cross-sectional survey approach was used in which data were collected from 424 employees of six state-owned polytechnics in the north central zone of Nigeria. Partial Least Squares Method (PLS) algorithm and bootstrap techniques were used to test the study's hypotheses. The results provided support for all the hypothesised relationships, except compensation-employee performance relationship and performance appraisal-employee performance relationship. The overall findings signified a positive effect of recruitment and selection, training and development, and succession planning on employee performance. The finding indicated that effective HR practices (recruitment and selection, training and development, and succession planning) enhanced employee performance; thus, organisations should entrench such HR practices in an effective manner. Besides, competitive compensation system, performance appraisal and succession planning weighted with management support would enhance employee performance, given that management support is recognized as a constant driver of employee creativity and innovation. Also, employee performance can be improved through management support because it gives employees a sense of involvement necessary for inspiring creative ideas, discovering new opportunities and converting them to action without losing efficiency at work. Limitation and recommendations of the study are also discussed.